Group meta-cognitive therapy and depression in women with breast cancer: a randomized controlled trial - Elham Zahedian; Masoud Bahreini; Nezamaddin Ghasemi; Kamran Mirzaei (BMC, 2021)
Abstract Background Breast cancer is one of the most common cancers in Iranian women. They will experience a mental health problem like depression before, during or after treatment. This study aimed to determine the effectiveness of group metacognitive therapy on depression, cognitive-emotional regulation, and meta-cognitive beliefs in women with breast cancer. Methods In this randomized controlled clinical trial, a total of 24 depressed patients with breast cancer were randomly allocated to experimental and control groups. The experimental group received meta-cognitive therapy in 8 weekly sessions, but the control group received treatment as usual. Beck Depressive Inventory, cognitive emotion regulation questionnaire, and meta-cognitions questionnaire were completed before, after and one month after the intervention. Data were analyzed using Wilcoxon and Chi-square tests. Results The mean score of depression in the experimental group was reduced from 21.6 ± 4.83 in the pre-test to 13.83 ± 8.12 in one-month follow-up (p = 0.16); however, there was no significant difference in the control group. The mean score of cognitive emotion regulation did not show a significant change in the two groups during the study and follow-up period. The mean score of meta-cognitive beliefs reached 68.75 ± 15.74 from 79.51 ± 10.72 in the experimental group during the follow-up period (p = 0.006); however, there was no significant difference in the control group in the score of metacognitive beliefs. Conclusion These findings support the efficacy of meta-cognitive therapy as a viable psychosocial intervention in depressed patients with breast cancer. Trial registration IRCT201606288473N5. Registered on: 05/09/2016 https://www.irct.ir/trial/8946 .